Oesophageal perforation: a rare complication of minor blunt trauma. Issue 4 (July 1996) - Cumberbatch, G L; Reichl, M
Abstract : Oesophageal perforation following blunt trauma is rare and accounts for less than 10% of all oesophageal ruptures. Review of published reports revealed only two cases of isolated oesophageal perforation after minor blunt trauma, and these were as a direct result of the Heimlich manoeuvre. This paper describes a case of perforation of the oesophagus as an isolated injury following blunt minor trauma.